A satellite-derived baseline of photosynthetic life across Antarctica - Walshaw, Charlotte V.; Gray, Andrew; Fretwell, Peter T.; Convey, Peter; Davey, Matthew P.; Johnson, Joanne S.; Colesie, Claudia (Nature Geoscience, 2024)
Terrestrial vegetation communities across Antarctica are characteristically sparse, presenting a challenge for mapping their occurrence using remote sensing at the continent scale. At present there is no continent-wide baseline record of Antarctic vegetation, and large-scale area estimates remain unquantified. With local vegetation distribution shifts now apparent and further predicted in response to environmental change across Antarctica, it is critical to establish a baseline to document these changes. Here we present a 10 m-resolution map of photosynthetic life in terrestrial and cryospheric habitats across the entire Antarctic continent, maritime archipelagos and islands south of 60° S. Using Sentinel-2 imagery (2017–2023) and spectral indices, we detected terrestrial green vegetation (vascular plants, bryophytes, green algae) and lichens across ice-free areas, and cryospheric green snow algae across coastal snowpacks. The detected vegetation occupies a total area of 44.2 km2, with over half contained in the South Shetland Islands, altogether contributing just 0.12% of the total ice-free area included in the analysis. Due to methodological constraints, dark-coloured lichens and cyanobacterial mats were excluded from the study. This vegetation map improves the geospatial data available for vegetation across Antarctica, and provides a tool for future conservation planning and large-scale biogeographic assessments.
Keywords: Antarktis; alger; biodiversitet; botanikk; lav; planter

Discovery of a large population of Hygrolembidium isophyllum (Lepidoziaceae, Marchantiophyta) in the South Shetland Islands, Antarctica - Putzke, Jair; Ramos Ferrari, Flávia; Schaefer, Carlos E. G. R. (Polar Research, 2020)
In February 2019, during fieldwork at Harmony Point, Nelson Island, South Shetland Islands, Antarctica, a large population of the rare liverwort Hygrolembidium isophyllum (Lepidoziaceae) was discovered. The occurrence of this rare species reinforces the need to preserve Antarctic Specially Protected Area 133.
Keywords: Antarktis; biologi; levermoser; miljøvern; planter

Nitrogen isotope fractionation explains the 15N enrichment of Antarctic cryptogams by volatilized ammonia from penguin and seal colonies - Bokhorst, Stef; van Logtestijn, Richard; Convey, Peter; Aerts, Rien (Polar Research, 2019)
Vegetation near bird and seal rookeries typically has high δ15N signatures and these high values are linked to the enriched δ15N values of rookery soils. However, Antarctic cryptogams are mostly dependent on atmospheric ammonia (NH3) and volatized NH3 from rookeries is severely depleted in δ15N-NH3. So there is an apparent discrepancy between the isotopically depleted source (NH3) and δ15N-enriched vegetation. In this article, we aim to resolve this discrepancy to better understand the mechanisms and processes involved in isotopic changes during nitrogen transfer between Antarctic marine and terrestrial ecosystems. Under laboratory conditions, we quantified whether volatized NH3 affects the isotopic signature of cryptogams. NH3 volatilizing from penguin guano and elephant seal dung was depleted (44–49‰) in δ15N when captured on acidified filters, compared to the source itself. Cryptogams exposed to the volatized NH3 were enriched (18.8–23.9‰) in δ15N. The moss Andreaea regularis gained more nitrogen (0.9%) than the lichen Usnea antarctica (0.4%) from volatilized NH3, indicating a potential difference in atmospheric NH3 acquisition that is consistent with existing field differences in nitrogen concentrations and δ15N between mosses and lichens in general. This study clarifies the δ15N enrichment of cryptogams resulting from one of the most important nitrogen pathways for Antarctic vegetation.
Keywords: Antarktis; fugler; kjemiske analyser; kryptogamer; lav; moser; planter; seler; økologi

Psoroma antarcticum, a new lichen species from Antarctica and neighbouring areas - Park, Chae Haeng; Hong, Soon Gyu; Elvebakk, Arve (Polar Biology, 2018)
Keywords: Antarktis; biodiversitet; botanikk; lav; moser; planter

Description of plant communities on Half Moon Island, Antarctica - Schmitz, Daniela; Putzke, Jair; Pereira de Albuquerque, Margéli; Schünemann, Adriano Luis; Costa Beber Vieira, Frederico; de Carvalho Victoria, Filipe de Carvalho Victoria; Batista Pereira, Antônio (Polar Research, 2018)
During February–March of the austral summers of 2013/14 and 2014/2015, fieldwork was performed on Half Moon Island, South Shetland Archipelago, Antarctica, to evaluate the distribution and abundance of mosses and lichens, as well as to describe and map the plant communities there. The quadrat (20 × 20 cm) sampling method was employed in a phytosociological study that aimed to describe these communities. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The number of species totalled 38 bryophytes, 59 lichens, only one flowering plant (Deschampsia antarctica Desv.), and two macroscopic terrestrial algae. Five types of plant communities were identified on the island, as follows: (1) fruticose lichen and moss cushion, (2) moss carpet, (3) muscicolous lichen, (4) crustose lichen and (5) moss turf.
Keywords: Antarktis; botanikk; bryozoa; flora; fytososiologi; lav; moser; planter; økologi

Patterns of fungal–algal symbiont association in Usnea aurantiaco-atra reveal the succession of lichen–moss communities in Fildes Peninsula, Antarctica - Cao, Shunan; Peng, Fang; Zheng, Hongyuan; Liu, Chuanpeng; Zhou, Qiming (Polar Research, 2017)
Usnea aurantiaco-atra is the most widespread flora in Fildes Peninsula. There are two growth types of U. aurantiaco-atra: the erect form on rocks and the prostrate form associated with mosses. Phylogenetic analysis showed that individuals of the two growth forms share genotypes. Moreover, haploid disequilibrium testing indicated no significant genetic difference for the two growth forms when fungal and algal internal transcribed spacer rDNA were treated as two alleles of one lichen individual. The two growth forms of U. aurantiaco-atra appear to reflect different stages of lichen–moss community succession. A mode is proposed for demonstrating the occurrence of this succession.
Keywords: Antarktis; botanikk; flora; fylogenetikk; lav; moser; planter

Adjustment of pigment composition in Desmarestia (Desmarestiaceae) species along a sub-Antarctic to Antarctic latitudinal gradient - Mansilla, Andrés; Méndez, Fabio; Murcia, Silvia; Rodriguez, Juan Pablo; Marambio, Johanna; Rosenfeld, Sebastián; Yokoya, Nair; Bischof, Kai (Polar Research, 2016)
Photosynthesis at high latitudes demands efficient strategies of light utilization to maintain algal fitness and performance. The fitness, and physiological adaptation, of a plant or algae species depends in part on the abundance and efficiency of the pigments it can produce to utilize the light resource from its environment. We quantified pigment composition and concentration in six species of the brown macroalgal genus Desmarestia, collected from sub-Antarctic sites (Strait of Magellan, Beagle Channel–Cape Horn Province) and sites on the Antarctic Peninsula and adjacent islands. Sub-Antarctic Desmarestia species exhibited lower concentrations of chlorophyll a, chlorophyll c and fucoxanthin than endemic Antarctic species. Antarctic samples of D. menziesii and D. antarctica collected along a decreasing latitudinal gradient showed spatial and interspecific differences in light-harvesting pigment composition. Our results suggest distinct physiological adjustments in Desmarestia species in response to heterogeneous abiotic environmental conditions. The marine sub-Antarctic and Antarctic ecosystems are characterized by harsh environments (e.g., extreme irradiance, photoperiod, temperature, salinity) to which the physiology of macroalgal species must adapt. Keywords: Macroalgae; Phaeophyceae; photosynthesis; physiology; environmental heterogeneity; Chile.
Keywords: Antarktis; alger; fotosyntese; fysiologi; planter

Methane and nitrous oxide fluxes in relation to vegetation covers and bird activity in ice-free soils of Rip Point, Nelson Island, Antarctica - Neufeld, Ângela Denise Hubert; de Godoi, Stefânia Guedes; Pereira, Antônio Batista; Bayer, Cimélio; Schünemann, Andriano Luis; de Carvalho Victoria, Filipe; de Albuquerque, Margéli Pereira; Camargo, Estefânia; Vieira, Frederico Costa Beber (Polar Research, 2015)
This study aimed to quantify the nitrous oxide (N2O) and methane (CH4) fluxes at sites with different vegetation covers and where bird activity was present or absent using the static chamber method, on Rip Point, Nelson Island, maritime Antarctic. The sites were soils covered by Sanionia uncinata, lichens, Prasiola crispa, Deschampsia antarctica and bare soil. Seabirds used the P. crispa and D. antarctica sites as nesting areas. Soil mineral N contents, air and soil temperature and water-filled pore space were measured, and the content of total organic C and particulate organic C, total N, bulk density and texture were determined to identify controlling variables of the gas emissions. The N2O and CH4 flux rates were low for all sampling events. Mean N2O flux rates ranged from 0.11±1.93 up to 21.25±22.14 µg N2O m−2 h−1 for the soils under lichen and P. crispa cover, respectively. For the CH4 fluxes, only the P. crispa site showed a low positive mean (0.47±3.61 µg CH4 m−2 h−1). The bare soil showed the greatest absorption of CH4 (−11.92±5.7 µg CH4 m−2 h−1), probably favoured by the coarse soil texture. Bare soil and S. uncinata sites had N2O accumulated emissions close to zero. Net CH4 accumulated emission was observed only at the P. crispa site, which was correlated with (p<0.001). These results indicate that seabird activity influences N2O and CH4 soil fluxes, while vegetation has little influence, and bare soil areas in maritime Antarctica could be greenhouse gas sinks. Keywords: Soil greenhouse gases; seabirds; vegetal cover; maritime Antarctica.
Keywords: Antarktis; biogeokjemi; drivhuseffekt; drivhusgasser; flora; global oppvarming; klimaendringer; klimagasser; planter; sjøfugler; økosystemer

Assessing the importance of human activities for the establishment of the invasive Poa annua in Antarctica - Molina-Montenegro, Marco A; Carrasco-Urra, Fernando; Acuña-Rodriguez, Ian; Oses, Rómulo; Torres-Diaz, Cristian; Chwedorzewska, Katarzyna J (Polar Research, 2014)
Because of its harsh environmental conditions and remoteness, Antarctica is often considered to be at low risk of plant invasion. However, an increasing number of reports have shown the presence and spread of non-native plants in Antarctica; it is therefore important to study which factors control the invasion process in this ecosystem. Here, we assessed the role of different human activities on the presence and abundance of the invasive Poa annua. In addition, we performed a reciprocal transplant experiment in the field, and a manipulative experiment of germination with P. annua and the natives Colobanthus quitensis and Deschampsia antarctica, in order to unravel the effects of physical soil disturbance on the establishment and survival of P. annua. We found a positive correlation between abundance of P. annua and level of soil disturbance, and that survival of P. annua was 33% higher in sites with disturbed soil than non-disturbed. Finally, we found that disturbance conditions increased germination for P. annua, whereas for native species germination in experimentally disturbed soil was either unchanged or reduced compared to undisturbed soil. Our results indicate that human activities that modify abiotic soil characteristics could play an important role in the abundance of this invasive species. If the current patterns of human activities are maintained in Antarctica, the establishment success and spread of P. annua could increase, negatively affecting native flora. Keywords: Alien species; Colobanthus quitensis; Deschampsia antarctica; human disturbance; Poa annua; tourists.
Keywords: Antarktis; biodiversitet; flora; menneskelig påvirkning; planter; turisme; økosystemer

Characterization and mapping of plant communities at Hennequin Point, King George Island, Antarctica - Victoria, Filipe de C; de Albuquerque, Margéli P; Pereira, Antonio B; Simas, Felipe N B; Spielmann, Adriano A; Schaefer, Carlos E G R (Polar Research, 2013)
King George Island is the largest island and the principal area used for research bases in Antarctica. Argentina, Brazil, Chile, China, Poland, Russia, South Korea and Uruguay have permanent open bases on this island. Other countries have seasonal summer stations on different parts of this island, which demonstrates that human impact is strong on King George Island relative to other areas in the maritime and continental Antarctica. The objective of this work was to present a phytosociological approach for ice-free areas of Hennequin Point, eastern coast of Admiralty Bay, King George Island. The study started with the classification and description of the plant communities based primarily on phytosociological and biodiversity data. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The plant communities were described as follows: (1) lichen and moss cushion formation; (2) moss carpet formation; (3) fellfield formation; (4) grass and cushion chamaephyte formation; and (5) Deschampsia Antarctica–lichen formation. Characterizations and distributions of the plant communities are presented on a map at a scale of 1:5000. The plant communities found at Hennequin Point, in general, differ from those found in other areas of the Admiralty Bay region, probably because of the concentration of skua nests in the area and the relief singularities. We conclude by highlighting the importance of the study of plant species found in the ice-free areas of the Antarctic with respect to environmental monitoring and for evaluating global climate and environmental changes. Keywords: Plant communities mapping; lichens; mosses; flowering plants; Antarctic
Keywords: Antarktis; biodiversitet; fytososiologi; klimaendringer; lav; miljøendringer; moser; planter; plantesosiologi

Ecosystem response to climatic change: the importance of the cold season - Bokhorst, Stef; Bjerke, Jarle W; Tømmervik, Hans; Preece, Catherine; Phoenix, Gareth K (Ambio, 2012)
Winter climate and snow cover are the important drivers of plant community development in polar regions. However, the impacts of changing winter climate and associated changes in snow regime have received much less attention than changes during summer. Here, we synthesize the results from studies on the impacts of extreme winter weather events on polar heathland and lichen communities. Dwarf shrubs, mosses and soil arthropods were negatively impacted by extreme warming events while lichens showed variable responses to changes in extreme winter weather events. Snow mould formation underneath the snow may contribute to spatial heterogeneity in plant growth, arthropod communities and carbon cycling. Winter snow cover and depth will drive the reported impacts of winter climate change and add to spatial patterns in vegetation heterogeneity. The challenges ahead lie in obtaining better predictions on the snow patterns across the landscape and how these will be altered due to winter climate change.
Keywords: Antarktis; biologi; botanikk; dyr; klimaendringer; leddyr; planter; snø; sopper; zoologi; økosystemer

Global southern limit of flowering plants and moss peat accumulation - Convey, Peter; Hopkins, David W; Roberts, Stephen J; Tyler, Andrew N (Polar Research, 2011)
The ecosystems of the western Antarctic Peninsula, experiencing amongst the most rapid trends of regional climate warming worldwide, are important “early warning” indicators for responses expected in more complex systems elsewhere. Central among responses attributed to this regional warming are widely reported population and range expansions of the two native Antarctic flowering plants, Deschampsia antarctica and Colobanthus quitensis. However, confirmation of the predictions of range expansion requires baseline knowledge of species distributions. We report a significant southwards and westwards extension of the known natural distributions of both plant species in this region, along with several range extensions in an unusual moss community, based on new survey work in a previously unexamined and un-named low altitude peninsula at 69º22.0’S 71º50.7’W in Lazarev Bay, north-west Alexander Island, southern Antarctic Peninsula. These plant species therefore have a significantly larger natural range in the Antarctic than previously thought. This site provides a potentially important monitoring location near the southern boundary of the region currently demonstrated to be under the influence of rapidly changing climate trends. Combined radiocarbon and lead isotope radiometric dating suggests that this location was most likely deglaciated sufficiently to allow peat to start accumulating towards the end of the 19th century, which we tentatively link to a phase of post-1870 climate amelioration. We conclude that the establishment of vegetation in this location is unlikely to be linked to the rapid regional warming trends recorded along the Antarctic Peninsula since the mid-20th century. Antarctic plants, distribution limits, peat accumulation, dating.
Keywords: Antarktis; hårgress; klimaendringer; perleurt; planter; økosystemer

Colonization and demographic structure of Deschampsia antarctica and Colobanthus quitensis along an altitudinal gradient on Livingston Island, South Shetland Islands, Antarctica - Vera, María Luisa (Polar Research, 2011)
The colonization capacity and demographic structure of populations of Deschampsia antarctica and Colobanthus quitensis were studied in different microhabitats between 10 and 147 m a.s.l. on Livingston Island, South Shetland Islands, near the Spanish Antarctic base Juan Carlos I, in February 2002. At the highest site (147 m a.s.l.), mean temperatures were about 1 ºC lower than at sea level. Both species are less common in inland areas and at the highest altitudes only occur at restricted sites that are frequently snow-free in the early austral summer. The diameters of the largest plants (C. quitensis cushions 7-8 cm ; D. antarctica tufts 10-11 cm) in the populations growing at the highest altitudes (110 and 147 m a.s.l.) suggest that these populations were established about 24-28 years ago. The largest diameter plants (Deschampsia 20 cm; Colobanthus 18 cm) were found at the lowest altitudes on deep soil. The presence of numerous seedlings and young individuals on the periphery of populations established several years ago or at recently colonized sites suggests an active process of expansion. There were more emerged seedlings of C. quitensis than of D. antarctica, but the density of established individuals was higher for D. antarctica, suggesting these species have different demographic strategies. Keywords: Antarctic vascular plants; altitude and habitat effect; colonization; population structure.
Keywords: Antarktis; biologi; flora; planter

Notes on two subantarctic pannariaceous lichens - Jørgensen, Per Magnus (Cryptogamie Mycologie, 2005)
It is shown by use of a newly discovered, old photo of the missing type that Siphulina orphnina (Hue) C. W. Dodge is identical with Pannaria caespitosa P. M. Jorg. The new combination Pannaria orphnina (Hue) R M. Jorg. is made, and the name neotypitied. Parmeliella austroshetlandica Sochting & Ovstedal is shown to be a species in the small subantarctic genus Peltularia R. Sant. (Coccocarpiaceae), and is transferred to that genus.
Keywords: Antarktis; biologi; botanikk; lav; planter

Additions and corrections to the Lichens of Antarctica and South Georgia - Øvstedal, Dag; Smith, Ronald I. Lewis (Cryptogamie, Mycologie, 2004)
The taxonomic listing given in Lichens of Antarctica and South Georgia (Øvstedal & Lewis Smith 2001) has been updated. 17 additional taxa of lichenised fungi are described, including several nomenclatural changes. 14 of these are considered as new records for the Antarctic and one is new to South Georgia. One is described as new to science.
Keywords: Antarktis; biogeografi; botanikk; lav; planter; taksonomi

Lichens of Antarctica and South Georgia : a guide to their identification and ecology - Øvstedal, Dag Olav; Smith, Ronald Lewis (Cambridge University Press, 2001)
Keywords: Antarktis; botanikk; lav; planter

Photosynthetic responses of selected Antarctic plants to solar radiation in the southern maritime Antarctic - Montiel, Pedro; Smith, Andrew; Keiller, Don (Polar Research, 1999)
The effects of UV-B exclusion and enhancement of solar radiation on photosynthesis of the two phanerogams which occur in the maritime Antarctic, Deschampsia antarctica and Colobanthus quitensis, and the moss Sanionia uncinats were investigated. Data on air temperature and solar radiation illustrate a drastic seasonal variation. Daily O3 column mean values and UV-B measured at ground level document the occurrence of the O3“hole” in the spring of 1997, with a concomitant increase in UV-B. The grass, D. antarctica, exhibited a broad temperature optimum for photosynthesis between 10–25°C while photosynthesis did not saturate even at high irradiance. The high water use efficiencies measured in the grass may be one of the features explaining the presence of this species in the maritime Antarctic. The net photosynthesis response to intercellular CO2 (A/ci) for D. antarctica was typical of a C3 plant. Exposure to a biologically effective UV-B irradiance of 0.74 W M-2 did not result in any significant change in either the maximum rate of photosynthesis at saturating CO2 and light, or in the initial carboxylation efficiency of Rubisco. (Vc,max). Furthermore while ambient (or enhanced) solar UV-B did not affect photochemical yield, measured in the field, of C. quitensis and D. antarctica, UV-B enhancement did affect negatively photochemical yield in S. uncinata. In D. antarctica plants, exposure to UV-B at low irradiances elicited increased flavonoid synthesis. The observed effects of UV-B enhancement on the moss (decreased photochemical yield) and the grass (increase in flavonoids) require further, separate investigation.
Keywords: Antarktis; botanikk; fotosyntese; klimaendringer; moser; planter

A new species of Parmelia (lichenized Ascomycotina) from the Antarctic - Øvstedal, Dag Olav; Elix, John A.; Smith, Ronald I. Lewis (Mycotaxon, 1998)
A new species of Parmelia (lichenized Ascomycotina) from the Antarctic. Parmelia lindsayana Ovstedal & Elix from Signy Island (South Orkney Islands) is described as new. This species resembles P. protosulcata Hale and P. cunninghamii Crombie, but differs in morphological details and in containing usnic, alpha-collatolic and alectoronic acids.
Keywords: Antarktis; Sør-Orknøyene; botanikk; lav; planter

Caloplaca Lewis-Smithii, a new lichen species from continental Antarctica - Søchting, Ulrik; Øvstedal, Dag Olav (Mycotaxon, 1998)
A new muscicolous lichen species, Caloplaca lewis-smithii Søchting & Øvst., is described from Victoria Land, continental Antarctica. It is characterized by a grey to blackish brown microlobate thallus and a blackish apothecial disk with a white pruinose thalline margin.
Keywords: Antarktis; botanikk; lav; planter; sopper

Cold resistance and metabolic activity of lichens below 0°C - Kappen, Ludger; Schroeter, Burkhard; Scheidegger, Christoph; Sommerkorn, Martin; Hestmark, Geir (Proceedings of the F3.1, F3.4, F2.4 and F3.8 Symposia of COSPAR Scientific Commission F, 1996)
Laboratory measurements show that lichens are extremely tolerant of freezing stress and of low-temperature exposure. Metabolic activity recovered quickly after severe and extended cold treatment. Experimental results demonstrate also that CO2 exchange is already active at around −20°C. The psychrophilic character of polar lichen species is demonstrated by optimum temperatures for net photosynthesis between 0 and 15°C. In situ measurements show that lichens begin photosynthesizing below 0°C if the dry thalli receive fresh snow. The lowest temperature measured in active lichens was −17°C at a continental Antarctic site. The fine structure and the hydration state of photobiont and mycobiont cells were studied by low-temperature scanning electron microscopy (LTSEM) of frozen hydrated specimens. Water potentials of the frozen system are in the range of or even higher than those allowing dry lichens to start photosynthesis by water vapor uptake at +10°C. The great success of lichens in polar and high alpine regions gives evidence of their physiological adaptation to low temperatures. In general lichens are able to persist through glacial periods, but extended snow cover and glaciation are limiting factors.
Keywords: Antarktis; botanikk; frostresistens; lav; planter; polarområdene

Two further bipolar lichens - Øvstedal, Dag Olav; Gremmen, Niek J M (Graphis scripta, 1995)
Keywords: Antarktis; botanikk; lav; planter

Solorina Spongiosa in Antarctica: An Extremely Disjunct Bipolar Lichen - Smith, R. I. Lewis; Øvstedal, Dag Olav (The Lichenologist, 1994)
The bipolar foliose lichen Solorina spongiosa (Sm.) Anzi is reported from James Ross Island, Antarctica, where it grows on moss. This is only the third known occurrence of this lichen from the Southern Hemisphere, the other localities being in Tierra del Fuego and New Zealand. Its morphology resembles that of the New Zealand population and arctic-alpine populations from the Northern Hemisphere, although there are some differences in apothecial and spore size. As elsewhere, it occupies base-rich habitats colonized by predominantly calcicolous mosses and lichens.
Keywords: Antarktis; botanikk; lav; moser; planter

Pertusaria signyae (Lichenes), a new species from the Antarctic - Øvstedal, Dag Olav; Smith, Ronald I Lewis (Nova Hedwigia, 1992)
A saxicolous Pertusaria species is described as new to science: P. signyae Ovst. from South Orkney Islands. It has an isidiate thallus, subglobose fertile verrucae with poriform apothecia, and contains 2'-0-methylperlatolic acid.
Keywords: Antarktis; Sør-Orknøyene; botanikk; lav; planter

Contributions to the Caloplaca flora of the western Antarctic region - Søchting, Ulrik; Øvstedal, Dag Olav (Nordic Journal of Botany, 1992)
Fourteen species of the lichen genus Caloplaca are recorded from the western Antarctic region and described morphologically and anatomically, viz.: C. ammiospila, C. approximata, C. athallina, C. cirrochrooides, C. citrina, C. isidioclada, C. lucens, C. millegrana, C. regalis, C. sublobulata, C. tenuis, C. aff. anchon-phoeniceon. Type specimens of critical species have been studied. A key is provided to the species. Caloplaca ammiospila and C. approximata are reported as new to the Antarctic region.
Keywords: Antarktis; botanikk; lav; planter

Eine neue Gyalecta-Art aus der Antarctis: G. pezizoides sp. n. (lichensierte Fungi, Gyalectaceae) - Vezda, A.; Øvstedal, Dag Olav; Smith, Ronald I Lewis (Nova Hedwigia, 1992)
A new species of the genus Gyalecta, G. pezizoides sp. n. (lichenized Fungi, Gyalectaceae), is described and illustrated. This new species is taxonomically near to the holarctic Gyalecta peziza (Mont.) Anzi.
Keywords: Antarktis; botanikk; lav; planter

The lichen genus Stereocaulon in Antarctica and South Georgia - Smith, Ronald I Lewis; Øvstedal, Dag Olav (Polar Biology, 1991)
Six species of Stereocaulon and one unnamed taxon (close to S. glabrum) are reported from South Georgia, the maritime Antarctic islands and Antarctic Peninsula. S. caespitosum is new to the western sub-Antarctic. Variations in morphology and secondary chemistry are provided, and the ecology and geographical distribution in the sub-Antarctic and Antarctic biomes are given for each taxon.
Keywords: Antarktis; botanikk; lav; planter

Virkninger av klimaendringer i polarområdene : bidrag til den interdepartementale klimautredningen - Kverndal, Arnt-Ivar; Elvebakk, Arve; Jaworowski, Zbygniew; Hansson, Rasmus (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; biologi; drivhuseffekten; dyreliv; fiskeri; flora; havbruksnæring; havis; havnivå; isbreer; klimaendringer; klimagasser; permafrost; planter; polarområdene; vannressurser; økologi

Microclimates and water budget of algae, lichens and a moss on some nunataks in Queen Maud Land - Gjessing, Yngvar; Øvstedal, Dag Olav (International Journal of Biometeorology, 1989)
Keywords: Dronning Maud Land; NARE 1984/85; alger; biologi; lav; mikroklima; moser; planter

Muscicolous Lepraria species and other leprarioid lichens in the Antarctic - Botnen, Astri; Øvstedal, Dag Olav (Polar Research, 1988)
Keywords: Dronning Maud Land; botanikk; forskning; lav; planter

Cladonia galindezii, a new Antarctic lichen species - Øvstedal, Dag Olav (Cryptogamie, Bryologieet Lichénologie, 1988)
Keywords: Antarktis; botanikk; lav; planter

On the variation of Ochrolechia parella in the western Antarctic and Subantarctic area - Øvstedal, Dag Olav (Polarforschung, 1988)
Keywords: Antarktis; botanikk; lav; planter

Botany of Bouvetøya, South Atlantic Ocean. II. The terrestrial vegetation of Bouvetøya - Engelskjøn, Torstein (Polar Research, 1987)
Keywords: Bouvetøya; botanikk; forskning; planter

Botany of two Antarctic mountain ranges: Gjelsvikfjella and Mühlig-Hofmannfjella, Dronning Maud Land. I. General ecology and development of the Antarctic cold desert cryptogam formation - Engelskjøn, Torstein (Polar Research, 1986)
Keywords: Dronning Maud Land; NARE 1984/85; botanikk; ekspedisjoner; forskning; planter

Zonality of climate and plant distributions in some Arctic and Antarctic regions - Engelskjøn, Torstein (Norsk Polarinstitutt, 1986)
Keywords: Bouvetøya; Dronning Maud Land; botanikk; klima; planter; polarområdene

Lichens and lichen parasites from the British-Swedish-Norwegian antarctic expedition 1949-52 to Dronning Maud Land - Øvstedal, Dag Olav (Cryptogamie: bryologie, lichenologie, 1986)
Keywords: Dronning Maud Land; botanikk; ekspedisjoner; lav; parasitter; planter

Botany of Gjelsvikfjella and Muhlig-Hofmannfjella, Dronning Maud Land - Engelskjøn, Torstein (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; botanikk; ekspedisjoner; planter

Some lichens from HU Sverdrup Mountains, Dronning Maud Land, Antarctis - Øvstedal, Dag Olav (Nova Hedwigia: Zeitschrift fur Kryptogamenkunde, 1983)
Keywords: Dronning Maud Land; botanikk; lav; planter

Some lichens from Vestfjella, Dronning Mauds Land, Antarctis - Øvstedal, Dag Olav (Cryptogamie. Bryologie, lichénologie, 1983)
Keywords: Dronning Maud Land; botanikk; lav; planter

A new Pannaria species from the Antarctic - Øvstedal, Dag Olav; Smith, Ronald Lewis (Cryptogamie, Bryologie, Lichenologie, 1983)
Pannaria austro-orcadensis Ovst., sp.nov., from the northern maritime Antarctic, is characterized by its purple-brown lobulate thallus, brown apothecia smooth spores and no secondary products. It grows on moist gravelly soil and bryophytes.
Keywords: Dronning Maud Land; botanikk; lav; planter

Lichens from Vestfjella, Dronning Maud Land - Lindsay, Denis Christopher (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; botanikk; lav; planter